(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2020)
The aim of the present research is to identify the degree of availability of the requirements of the application of knowledge management approach in secondary schools in Lattakia city from the perspective of teachers، as well as the views of teachers in secondary schools on the availability of requirements to apply the knowledge management approach according to the research variables (type of training courses followed by teachers) ، Years of experience، educational and educational qualification). To achieve the objectives of the research، the researcher used the descriptive (analytical) approach to suit the research topic. The researcher also designed a questionnaire to measure the degree of availability of the requirements of the application of knowledge management approach، consisting of (47) phrases distributed over (4) axes، and an open question about the proposed ways to provide the requirements of the application of management. Knowledge in secondary schools، distributed to a sample of (390) teachers. The results of the research confirmed that the degree of availability of the requirements of applying the knowledge management approach in secondary education schools in Lattakia was medium on the questionnaire as a whole، as well as for the axes: organizational culture، organizational structure، and administrative leadership. The focus of information technology was low availability. The research results also showed that there were differences in the views of the respondents on the degree of availability of the requirements of applying the knowledge management approach in secondary schools due to the educational qualification variable for the benefit of the diploma educational qualification holders، while there were no differences in the views of the sample members attributed to the variables of the type of courses. The researcher reached a number of proposals to provide the requirements for applying the knowledge management approach in secondary education schools, including: the necessity of training courses and workshops to spread the culture of knowledge among high schools to keep pace with developments and adapt them to their needs, and work to provide computers and infrastructure to facilitate the processes of knowledge sharing, sharing and application. هدف البحث الحالي إلى تعرّف درجة توافر متطلبات تطبيق مدخل إدارة المعرفة في مدارس التعليم الثانوي في مدينة اللاذقية من وجهة نظر المدرسين، وكذلك تعرّف وجهات نظر المدرسين في المدارس الثانوية حول مدى توافر متطلبات تطبيق مدخل إدارة المعرفة حسب متغيرات البحث (نمط الدورات التدريبية التي اتبعها المدرسين، عدد سنوات الخبرة، والمؤهل العلمي والتربوي). لتحقيق أهداف البحث استخدمت الباحثة المنهج الوصفي (التحليلي) لملاءمته لموضوع البحث، كما قامت بتصميم استبانة لقياس درجة توافر متطلبات تطبيق مدخل إدارة المعرفة، تكوّنت الاستبانة من (47) عبارةً موزعةً على (4) محاور، وسؤال مفتوح الهدف منه معرفة السبل المقترحة لتوفير متطلبات تطبيق مدخل إدارة المعرفة في مدارس التعليم الثانوية، وتم توزيعها على عينة مكونة من (390) مُدّرساً. أكدت نتائج البحث أن درجة توافر متطلبات تطبيق مدخل إدارة المعرفة في مدارس التعليم الثانوي في مدينة اللاذقية جاءت بدرجة متوسطة على الاستبانة ككل، وكذلك بالنسبة لمحاور: الثقافة التنظيمية، الهيكل التنظيمي، والقيادة الإدارية. أما محور تكنولوجية المعلومات فقد جاء بدرجة توافر منخفضة. كما بينت نتائج البحث أيضاً وجود فروق في وجهات نظر أفراد عينة البحث حول درجة توافر متطلبات تطبيق مدخل إدارة المعرفة في المدارس الثانوية تعزى لمتغير المؤهل العلمي التربوي لصالح حملة دبلوم التأهيل التربوي، في حين لم يكن هناك فروق في وجهات نظر أفراد العينة تعزى لمتغيري نمط الدورات التدريبية التي اتبعها المدرسون وعدد سنوات الخبرة، وتوصلت الباحثة إلى عدد من المقترحات لتوفير متطلبات تطبيق مدخل إدارة المعرفة في مدارس التعليم الثانوي، ومنها: ضرورة قيام دورات تدريبية وورش عمل لنشر ثقافة المعرفة بين المدارس الثانوية لمواكبة التطورات وتكييفها مع احتياجاتها، والعمل على توفير حواسيب وبنية تحتية تُسّهل عمليات نشر المعارف وتشاركها وتطبيقها.